Engagement and the workaholism in human resources professionals - Claudia Duarte Vergara; Augusto Gilmar Antunes Althoff; Luana Giongo Pedrotti; Ana Claudia Souza Vazquez; Mônica Maria Celestina De Oliveira (Revista Psicologia, 2020)
The main goal of this study was to evaluate the level of engagement and workaholism and its correlations with personal resources, job resources and job demands in Human Resources professionals. In this study, 440 HR professionals participated, being 80% women from Brazil’s five region. The findings suggest that HR professionals show an average level of engagement with the work they do, which is compatible with self-esteem, optimism, self-efficacy and hope. Besides, they also show an average level of workaholism, which demonstrates that excessive and compulsive work is something real in their everyday routine. People over 40 years old showing a lower average level of engagement, which was unexpected since this age group is supposed to be solid careers. Moreover, a positive and weak correlation with workaholism was found, which suggests the influence of excessive and compulsive work at the way energy is activated. Suggestions are presented for further studies in the area.